2016
DOI: 10.1049/iet-map.2015.0785
|View full text |Cite
|
Sign up to set email alerts
|

Built‐in antenna design for 2.4 GHz ISM band and GPS operations in a wrist‐worn wireless communication device

Abstract: A compact monopole and inverted‐F antenna design for 2.4 GHz ISM band (2400–2485 MHz) and 1.575 GHz GPS operations suitable to be embedded within a wrist‐worn wireless communication device is presented. Those antennas are fabricated on a polycarbonate and acrylonitrile‐butadiene‐styrene blend substrate with a three‐dimensional etching process for irregular plastic materials. The wrist‐worn device with and without a solid hand phantom model is evaluated. The radiation efficiency of the antennas can reach 80% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…RF switches were implemented to enable dual-polarized characteristics on the probe-fed GPS antenna, which is designed to be part of jackets and raincoats. A three-dimensional LP antenna structure working on both GPS/WLAN bands 9 for wrist-worn application [86]. This dual band and the dualfeed antenna evaluated on human hand-phantom exhibited reasonable radiation performance in term of its gain and efficiency.…”
Section: Wearable Single and Dual Polarized Antennasmentioning
confidence: 99%
“…RF switches were implemented to enable dual-polarized characteristics on the probe-fed GPS antenna, which is designed to be part of jackets and raincoats. A three-dimensional LP antenna structure working on both GPS/WLAN bands 9 for wrist-worn application [86]. This dual band and the dualfeed antenna evaluated on human hand-phantom exhibited reasonable radiation performance in term of its gain and efficiency.…”
Section: Wearable Single and Dual Polarized Antennasmentioning
confidence: 99%
“…This will bring a challenge because the space allowed by wrist-worn devices with embedded antenna is very limited. In the latest research papers in the past five years, we observed that the antenna design for watch application almost only single band as ISM (industrial, scientific and medical, 2.4 GHz) or GPS (global positioning system) band [16][17][18][19][20][21][22]. Although there are smart watch devices design with wideband code division multiple access (WCDMA) and long-term evolution (LTE) applications, in the recent literature, only a single frequency band or a specific frequency band with a small bandwidth are designed in these antennas design [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. , a built‐in antenna works perfectly in GPS and ISM band, the antenna is built with complex materials and it is suitable for wearable devices such as smart watch.…”
Section: Introductionmentioning
confidence: 99%